ANALISIS MANAJEMEN PELAYANAN PEMERIKSAAN KLASIFIKASI ATLET PENYANDANG DISABILITAS DI NATIONAL PARALYMPIC COMMITTEE INDONESIA PROVINSI LAMPUNG - M Tasa Kasumbang; Efraldo Yudistira; Bota Muhammad Akbar; Al Um Aniswatun Khasanah; Muhammad Faris Nuuruddin; Nabila Nur Afifah Fitri (Journal of Hospital Administration and Excellent Health Service, 2026)
Introduction: Athlete classification is a fundamental component of para-sports, ensuring fair competition by determining athletes' eligibility based on functional abilities according to the International Paralympic Committee (IPC) standards. At the regional level, classification requires not only accurate clinical assessment but also efficient health service management. However, the classification process at the National Paralympic Committee of Indonesia (NPCI) Lampung Province still faces challenges related to scheduling, infrastructure, and administrative management. Objective: This study aimed to analyze the health service management of athlete classification and propose strategies to improve service efficiency at NPCI Lampung Province. Methods: A qualitative descriptive approach was employed. Data were collected through in-depth interviews, observations, focus group discussions, and document reviews involving NPCI administrators, medical classifiers, physiotherapists, technical classifiers, and para-athletes. Data were analyzed using the Miles, Huberman, and Saldaña interactive model. Results: Three major challenges were identified, including scheduling inconsistencies, limited examination infrastructure, and paper-based administrative management. Based on these findings, an Integrated Para-Classification System (IPCS) was proposed to integrate administrative processes, medical screening, physiotherapy assessment, technical classification, and documentation into a single service pathway. Conclusion: The proposed integrated service model has the potential to improve service efficiency, strengthen multidisciplinary collaboration, and enhance the quality of athlete classification management at NPCI Lampung Province.